Poverty Vis-a-vis Livelihood in the Rural Context of Nepal: At a Glance - Prasin, JN (Himalayan Journal of Sociology and Anthropology, 2009)
Himalayan Journal of Sociology & Anthropology Vol.2 2005 p.48 No Abstract available